Preliminary investigation on industrial properties of the olode-falansa pegmatite, southwestern Nigeria (2004)
In olode-falansa area, which is part of the southwestern basement complex of Nigeria near Ibadan, the major rock types are granite gneiss, quartzite, mediun-grained granite and pegmatite. In particular, the pegmatites which occur as low-lying bodies, with a mineralogy dominated by pinkish-white microcline perthite, quartz, muscovite and plagioclase plus accessory constituents of garnet, beryl and tourmaline have been investigated for their distribution, physical, chemical and mineralogical characteristics in order to evaluate their industrial qualities. Chemical analysis shows variations in the major elements contents of the main minerals. In particular, quarta samples have 64.02 to 97.30% SiO2; 0.86 to 2.60% Ai2O3, 0.05 to 1.02% K2O and 0.13 to 1.29% Fe2O3 while the feldspar samples are61.37 to 67.83% SiO2; 16.85 to 18.40% AI2O; 11.35 to 14.32% K2O and 0.04 to 0.11% Fe2O3 respectively. The total alkalis (Na2O+k2O) indicate k-feldspar composition. The specific gravity for quartz ranges from 2.60-2.63, while that of feldspar is from 2.55-2.58. Water absorption capacity is higher for quartz (25.10-27.10%) than feldspar (4.61-5.80%). Compressive strength of selected pegmatite minerals indidcates values from 133.24 to 223.84MN/m2. The investigation shows that the pegmatites have good potential for industrial uses. They can be used directly as raw materials or after beneficiation. In particular, the quartz and feldspar can find application in the refractory, glass, ceramic and abrasive industries. They can also be found useful in minor construction works especially in homes and offices. Muscovite can be used as thermal and electrical insulators while the beryl can be useful as ornaments. The associated rocks such as gneisses, quartzites and granites can be useful in interior and exterior decorations as well as tiles manufacturing.